O sofrimento gera luta: o impacto da anemia falciforme e da vivência do adoecimento no desenvolvimento psíquico de portadores da doença - Rosa, Jéssica Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The sickle cell anemia is a chronic, serious illness, considered to be the most common hereditary monogenic disease in Brazil. This disease, which is characterized by a structural alteration on the beta globin chain that leads to production of an abnormal hemoglobin (HbS), may induce in its bearers several health conditions: sickle cell crisis, infections, pulmonary hypertension, cardiovascular and kidney diseases, and many others. The brain may also be affected: strokes, silent cerebral infarcts and ischemic lesions are some of the possibly associated conditions, that may produce deficits on the development of the cognitive functions and decline in academic performances. As sickle cell anemia originated in Africa, it is more prevalent among people of African ancestry - a population which, historically, constitutes one of the most socially and economically vulnerable strata of the Brazilian society. Considering that every illness, its course and treatment exposes social relations and life conditions in a certain society; and that the expression of any disease relies not only on biological but also on psychological, economical and social factors, we deem as necessary to understand how the sickle cell anemia - for a long time subdiagnosed e little investigated - expresses itself in the contemporary society and on the lives of the patients. Adopting the psychological development as the category of study, within a dialectical and materialistic approach on the Socialhistorical Psychology; the life history method and the semi-structured interview for data collection, our goal was to investigate the most proeminent aspects of the psychological development process on sickle cell anemia patients, and their relationship with that illness. The results point to an expressive subjection of part of this population to conditions, situations and determiners that interfere and may cause important limitations not only to their psychological ...

A anemia falciforme é uma doença crônica e grave, considerada a doença hereditária monogênica mais comum no país. Determinada por uma alteração estrutural na cadeia da betaglobina que leva à produção de uma hemoglobina anormal (HbS), essa doença ocasiona diversos problemas de saúde a seus portadores: crises de dor, infecções, hipertensão pulmonar, doenças cardíacas e complicações renais, entre outras. O cérebro é também bastante afetado: dentre os problemas relatados, destacam-se acidentes vasculares cerebrais, infartos silenciosos e lesões isquêmicas, além de déficits no desenvolvimento das funções cognitivas que podem interferir no desempenho escolar e acadêmico. A anemia falciforme teve origem na África e é, portanto, estatisticamente mais prevalente na população negra - população essa que, historicamente, constitui as camadas mais vulneráveis social e economicamente do Brasil. Considerando que as doenças, seu curso e tratamento explicitam relações sociais e condições de existência em uma dada sociedade; e que a expressão de qualquer forma de adoecimento depende não só de fatores biológicos, mas também de psicológicos, econômicos e sociais, faz-se necessário compreender de que forma a anemia falciforme - por muito tempo subdiagnosticada e pouco pesquisada - se expressa na sociedade contemporânea e na vida de seus portadores. Tendo como categoria de estudo o desenvolvimento do psiquismo a partir do referencial materialistadialético e da Psicologia sócio-histórica; como método de coleta de dados a história de vida; e como técnica a entrevista semi-estruturada, buscou-se investigar os aspectos que mais se destacassem no processo de desenvolvimento do psiquismo dos portadores desta doença, e sua relação com a experiência do adoecimento. Os resultados apontaram para expressiva sujeição de parte desta população a condições, situações e fatores que interferem e podem vir...
The suffering leads to fighting
Keywords: Anemia falciforme; Doenças cronicas; Psicopatologia; Psicologia social; Saúde pública; Psychology, Pathological